2015
DOI: 10.1038/ncomms8389
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nucleotide metabolism by mutant p53 contributes to its gain-of-function activities

Abstract: SUMMARY Mutant p53 (mtp53) is an oncogene that drives cancer cell proliferation. Here we report that mtp53 associates with the promoters of numerous nucleotide metabolism genes (NMG). Mtp53 knockdown reduces NMG expression and substantially depletes nucleotide pools, which attenuates GTP dependent protein (GTPase) activity and cell invasion. Addition of exogenous guanosine or GTP restores the invasiveness of mtp53 knockdown cells, suggesting that mtp53 promotes invasion by increasing GTP. Additionally, mtp53 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 63 publications
(88 reference statements)
7
112
0
Order By: Relevance
“…Several studies demonstrated that gain-of-function (GOF) p53 mutants regulate cellular and nucleotide metabolism (148150). Using a three-dimensional (3D) culture model, Freed-Pastor et al discovered that breast cancer cell lines expressing either p53 R273H or p53 R280K disrupted acinar morphology through upregulation of the mevalonate pathway, which is responsible for cholesterol synthesis (148).…”
Section: Targeting P53 “Gain-of-function” Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies demonstrated that gain-of-function (GOF) p53 mutants regulate cellular and nucleotide metabolism (148150). Using a three-dimensional (3D) culture model, Freed-Pastor et al discovered that breast cancer cell lines expressing either p53 R273H or p53 R280K disrupted acinar morphology through upregulation of the mevalonate pathway, which is responsible for cholesterol synthesis (148).…”
Section: Targeting P53 “Gain-of-function” Pathwaysmentioning
confidence: 99%
“…Given that wildtype p53 could activate AMPK activity through transcriptional activation of the gene encoding β subunit of AMPK (152), these results strongly support a transcription-independent mechanism by which mutant p53 promotes tumor progression by activating cancer cell metabolism. Regulation of nucleotide metabolism by mutant p53 was recently found to be functionally important for GOF activities (150). CHIP-seq analysis of mutant p53 knockdown breast cancer cells demonstrated that loss of mutant p53 reduced many nucleotide metabolism genes (NMGs) and substantially depleted nucleotide pools, which attenuated GTP-dependent protein activity and cell invasion (150).…”
Section: Targeting P53 “Gain-of-function” Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…28 More than 50% of human tumors have a mutated form of p53 (mtp53) that is more stable and has gain-of-function activities such as promoting cell growth, chemotherapy resistance, angiogenesis, and metastasis. 29,30 An alternative mechanism by which p53 is thought to be inactivated in human cancers is through increased expression of MDM2. To date, there are 92 mutations in the MDM2 gene reported in the Catalog of Somatic Mutations in Cancer (COSMIC) website.…”
Section: Introductionmentioning
confidence: 99%